Secondary voltage control based on adaptive neural pi controllers (2010)
This paper’s aim is to present the performance of a Bspline neural network controller to regulate the reactive power provision from synchronous machines. Due to the fact that power systems work with nonstationary parameters and changing settings, adaptive control schemes are preferred. Control technology must ensure its performance in terms of power system’s operation to address the diversity of loads and the optimal utilization of the available resources. The B-spline neural network is an efficient tool to implement the adaptive control voltage, with the possibility of carrying out this task on-line taking into account the systems' nonlinearities. The reactive power dispatch is based on the premise that each machine must provide a proportion according to its nominal operating capacity. The applicability of the proposal is demonstrated by simulation on a 9buses 3-machines power system.